Annual Report on surveillance for Avian Influenza in poultry and wild birds in Member States of the European Union in 2019. (15th December 2020) - ,; Baldinelli, Francesca; Papanikolaou, Aleksandra; Stoicescu, Anca; Van der Stede, Yves; Aznar, Inma
Abstract: Context. Avian influenza (AI) is an infectious viral disease that affects all species of domestic and wild birds. The viruses causing this disease can be of high (HPAI) or low (LPAI) pathogenicity and represent a continuous threat to poultry in Europe. Council Directive 2005/94/EC requires EU Member States (MSs) to carry out surveillance in poultry and wild birds and notify the results to the responsible authority. Therefore, MSs, Iceland, Norway, Switzerland and the United Kingdom have implemented ongoing surveillance programmes to monitor incursions of AI viruses in poultry and wild birds. EFSA received a mandate from the European Commission to collate, validate, analyse and summarise the data resulting from the avian influenza surveillance programmes in an annual report. Poultry. Overall 24, 419 poultry establishments (PEs) were sampled, of which 87 were seropositive for H5 virus strains and 22 for H7 strains. Seropositive PEs were found in eight MSs (Belgium, Bulgaria, Denmark, France, Germany, the Netherlands, Poland, Spain) and the United Kingdom (also a MS at the time of collection). The highest percentage of seropositive PEs was found in establishments raising waterfowl game birds and breeding geese. Out of the 109 PEs with positive serological tests for H5/H7, only two tested positive in PCR and virology for H5/H7 virus strains, both of which were LPAI strains (H5N1 and H7N7, respectively) and were reported by Denmark. In addition, 12 countries also reported PCR results from 653 PEs carried out either as a screening test or subsequent to a negative serological test result. Five of these PEs were found positive for AI viral RNA: four H5N8 HPAI in Bulgaria and one H7N3 LPAI in Italy. Wild birds. A total of 19, 661 dead/moribund wild birds were sampled, with one bird testing positive to HPAI virus H5N6, which was reported by Denmark. In addition, there were 84 birds testing positive for LPAI H5 or H7 virus and 848 birds testing positive for non‐H5/H7 AI virus, reported by 30 countries. The surveillance findings for poultry and wild birds for 2019 are discussed in relation to findings from previous years and current knowledge of the epidemiology of AI in Europe.